SOCIALIZATION AND SELF-REALIZATION OF PERSONALITY IN CONSTRUCTS OF SCIENTIFIC SEARCH AND SCIENTIFIC-PEDAGOGICAL RESEARCH - Lyubov Sudyina; Nikolay Kozyrev; Olga Kozyreva (Вестник Северо-Кавказского федерального университета)
The article identifies opportunities for improving the quality of solving the tasks of personal development in the system of continuous education, identifies features of socialization and self-realization of the person through a personified, level inclusion of the personality in the system of technologies and products of scientific search and scientific research. Scientific-pedagogical research and scientific research in technical subjects determine the product of a person's activity - the basis for the acme-verification of the quality of socialization and self-realization of a person. The possibilities of socialization and self-realization of the individual in the system of continuous education are clariied through the features of the student's inclusion in the system of scientific search and scientific research; a level model of socialization and self-realization of the individual in the system of continuous education and professional-labor relations is presented. The pedagogical conditions for optimizing the quality of socialization and self-realization of the individual in the constructs of scientiic, pedagogical and scientiic and technical research are determined. The speciicity of socialization and self-realization of the individual is specified in the structure ofusing the technology ofsystem-pedagogical modeling, personified features of the formation of a culture of self-dependent work of the individual.